Critical aspects of radon remediation in karst limestone areas: some experiences in schools of South Italy. (24th January 2017) - Tunno, Tiziana; Caricato, Anna Paola; Fernandez, Manuel; Leonardi, Federica; Tonnarini, Sabrina; Veschetti, Miriam; Zannoni, Giovanni; Trevisi, Rosabianca
Abstract: The final results of radon monitoring in 438 schools located in the province of Lecce (Puglia Region, South Italy) showed an average radon concentration of 215 ± 20 Bq m −3 and that 7% of schools exceeded 500 Bq m −3, the current Italian action level for radon in workplaces, and consequently required remedial actions. The activity described in the present paper includes the main elements of the remediation project in a subgroup of school buildings. The main radon control systems adopted were sub-slab depressurization (in 57% of schools) and the active ventilation of the crawlspace (in 21% of schools). This experience allows us to put in evidence relevant critical aspects, such as the influence of the karstic nature of the area, the optimization of remediation, the architectural constraints in the case of buildings of architectural or historical interest, which are discussion herein. Moreover, considering the new reference level for radon in workplaces introduced by the new EU Basic Safety Standards, a new analysis of data, achieved in the first survey, highlighted that 20% of schools need to be remediated.